SOCIAL AND WORK ADAPTATION OF THE GRADUATES FROM THE TECHNICAL AND INFORMATIONAL EDUCATION FACULTY - Henryk, NOGA (Trends in education, 2013)
Research shows some tendencies in a teacher's job pointing both at the advantages and disadvantages or lacks of his/her activities. It seems that whether a young teacher's job is successful or not depends mostly on the school environment, which, in the majority of cases, in not simply a matter of choice for a candidate. A university graduate usually enters a place with long established working conditions. He or she thus comes into a school and classroom where students follow certain teaching and educational standards. What is important at this stage of one's professional development is a friendly cooperation with the head teacher, other colleagues and students' parents.
Keywords: adaptation; Technical and Informational Education; work preparation